Circulating tumor cells (CTCs) and red blood cells (RBCs) interactions and their potential clinical applications: a scoping review - Mohd Mahayudin, Muhammad Ashraf Samwil; Rahmat Sam, Mohd Fuad (IIUM Press, International Islamic University Malaysia, 2024)
Background: Circulating tumor cells (CTCs) are rare tumor cells that spread cancer through the bloodstream. As for red blood cells (RBCs), they play a crucial role in oxygen transport and interaction with cancer cells. CTCs adhere to RBCs, increasing survival and metastasis. Physical interactions and hemodynamic forces influence the distribution and circulation of CTCs, triggering immune responses and activating red blood cells, promoting tumor growth and metastasis. These interactions have significant clinical applications. Previous studies proved that the interactions between RBCs and CTCs were observed. These findings may be a new understanding and development in cancer studies. Therefore, this scoping review aims to identify on how those interactions remain in the body system that may be the metastasis contribution towards CTCs. Methods: This study will focus on scoping review that involves a few articles and research papers that have been filtered from online databases such as Scopus, ScienceDirect and PubMed. The process of selecting articles will be followed by Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) 2020 guidelines. Experimental research articles published in English between 2018 until 2023 will be included in this study to be reviewed. Results: Throughout the screening process, 7 articles were retrieved as included articles in this paper. Across the study, it showed that RBCs play a different role in the interactions with CTCs that contribute to the cell metastasis and survival. Additionally, a few interactions with different types of cancer cells were reported in the study that were clearly unexplored in other studies. These studies used different approach on how to conduct the studies but not to mention that similarly they used in vitro as the part of study model. Conclusion: From this review, it can be concluded that interactions of RBCs and CTCs were great findings in cancer studies. In the future, continuous study on the interactions may come across with therapeutic therapy study that may help in cancer therapy.